TINDAK TUTUR LOKUSI DAN ILOKUSI DALAM FILM MERRY RIANA: MIMPI SEJUTA DOLAR - Novanti Adzania Sari; Ika Febriani (Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study is to describe the forms of locutionary and illocutionary speech acts in the film Merry Riana: Dream of a Million Dollars. This research method is a qualitative descriptive method. Data in this study is speech acts of actors in the film Merry Riana: Dream of a Million Dollars. This data given from allow application you tube. The data collection techniques used are documents, listening techniques, and note-taking techniques. The data were analyzed through the stages of data reduction, data presentation, and conclusions or verification. The validity of the data was tested by extending observations and increasing persistence. The results in this study there are forms of locutionary and illocutionary speech acts. The form of locutionary speech acts in this study in the form of providing information or being informative. There are five forms of illocutionary speech acts in the study, namely assertive, directive, expressive, commissive, and declaration.